Olimpíadas de Matemática: concepção e descrição de “situações olímpicas” com o recurso do software Geogebra - Oliveira, Cícera Carla do Nasimento (2016)
In this work we propose the Mathematics Olympics, the educational context, from a methodological view through the Theory of Didactic Situations (TSD), where the structure of classes follows the first two phases of Didactic Engineering (ED): the previous analysis and a priori analysis. We seek to carry out the description of just TSD problems that possess the ability to use the Geogebra software, where this is not a propitious tool to encourage the intuitive reasoning, thus our research aimed to accomplish three things: identify the right problems to use the program , perform the commands in GeoGebra for the proposed activities and the description of the Olympic situation. Due to the increase in the number of participants of the Mathematical Olympiad Public Schools (OBMEP) each edition, we understand that it is necessary to address Olympic topics often in class, solving problems that context in order to develop a mechanism of incentives and learning by our students, so we believe that the resulting material of this research promotes the use by the teacher. We believe that the resolution of each Olympic problematic is an object to be researched and exploited by the learner, so it is up to the teacher indicating means to facilitate this route.